Design and durability analysis of marine concrete. Issue 1 (August 2020) - Zhao, Xirui; Gao, HuaXi; Fan, Wei; Duan, Yue; Shang, Ziqi; Hou, Jinglong
Abstract: Marine engineering is an important way for a country to go deep blue. In the marine environment, there are many factors that affect the durability of concrete, among which the most harmful one is chloride ion erosion. In order to improve the ability to resist chloride ion permeation, this paper designs, compares and selects the appropriate water cement ratio of marine concrete, with the use of new anticorrosive technologies such as epoxy coating and silane impregnation. The design service life and the chloride ion diffusion coefficient prediction are analysed by establishing models, and this paper verifies whether the engineering design meets the service life requirement.